Codependency and Validating Spann-Fischer in The Women of Mashhad - S Mhammad hasan Ashraf (Drug Control Headquarters, Research and Education Office, 2010)
Objective: The aim of this study is validating Spann-Fischer (codependency test) and investigating the "codependency" based on characteristics of the substance abuser wives. Methods: Spann-Fischer test normalize using a sample of 507 women. A sample contain of 204 women with addicted husbands who had referred to 33 qutting centers in Mashhad were analyzed and they also were used to validate the test. Results: The results confirm the validity and reliability of Spann-Fischer test, significant. Conclusion: The results emphasize the role of codependency as a factor against addiction treatment.